2009
DOI: 10.1111/j.1525-139x.2009.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

ASDIN: Patency Rates for Angioplasty in the Treatment of Pacemaker‐Induced Central Venous Stenosis in Hemodialysis Patients: Results of a Multi‐Center Study

Abstract: While hemodialysis access ligation has been used to manage pacemaker (PM) and implantable cardioverter-defibrillator (ICD) lead-induced central venous stenosis (CVS), percutaneous transluminal balloon angioplasty (PTA) has also been employed to manage this complication. The advantages of PTA include minimal invasiveness and preservation of arteriovenous access for hemodialysis therapy. In this multi-center study we report the patency rates for PTA to manage lead-induced CVS. Consecutive PM/ICD chronic hemodial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 27 publications
1
69
0
1
Order By: Relevance
“…22,23 Elevated venous pressure and high recirculation rates representing arteriovenous access dysfunction in patients with transvenous cardiac devices have been reported. 22 Drew et al 6 reported that angiography showed central vein stenoses in 21 of 34 (62%) patients. Most (n 5 17) of these were ipsilateral to the cardiac device.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22,23 Elevated venous pressure and high recirculation rates representing arteriovenous access dysfunction in patients with transvenous cardiac devices have been reported. 22 Drew et al 6 reported that angiography showed central vein stenoses in 21 of 34 (62%) patients. Most (n 5 17) of these were ipsilateral to the cardiac device.…”
Section: Discussionmentioning
confidence: 98%
“…The central venous stenosis can involve the subclavian and brachiocephalic veins, as well as the superior vena cava (Figs 1 and 2). 22 Although percutaneous balloon angioplasty and stent placement have been used to treat central venous stenosis, it frequently recurs. In a large multicenter study investigating angioplasty to treat central venous stenosis, primary patency rates were just 18% and 9% at 6 and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transluminal balloon angioplasty and thrombolytic therapy has also been employed to manage this complication (15). Successful pacing lead implantation has been reported after angioplasty and stent dilation of superior vena cava and innominate vein obstructions (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 14 ESRD patients with a pacemaker on the same side as AVF [11], 10 patients (71%) developed symptomatic venous hypertension and demonstrated subclavian vein stenosis or occlusion on angiography. Venous hypertension due to AVF and ipsilateral CIED leads has been in fact described in numerous other reports [14-18]. A possible explanation for SVC development beside vein injury during implantation is that repeated traumatization by leads in the vein wall is responsible for the progressive fibrotic stenosis just above the right atrium.…”
Section: Discussion/conclusionmentioning
confidence: 96%